2001
DOI: 10.1017/s1355617701733024
|View full text |Cite
|
Sign up to set email alerts
|

Working memory deficits associated with chronic fatigue syndrome

Abstract: Cognitive impairments are among the most frequently reported and least investigated components of the chronic fatigue syndrome (CFS). As part of a multifaceted study of the CFS, the present study investigated the cognitive functioning of chronic fatigue patients. The performance of 20 CFS patients was compared to that of controls (N = 20) on 4 tests of working memory (WM). Digit Span Forward was used to assess the storage capacity of WM. Multiple aspects of central executive functioning were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 59 publications
(126 reference statements)
8
29
0
1
Order By: Relevance
“…These results are consistent with previous studies (Busichio, et al, 2004;Claypoole, et al, 2007;Dobbs, Dobbs, & Kiss, 2001), providing more evidence of cognitive deficits in people with CFS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with previous studies (Busichio, et al, 2004;Claypoole, et al, 2007;Dobbs, Dobbs, & Kiss, 2001), providing more evidence of cognitive deficits in people with CFS.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies show impairments in memory (Claypoole et al, 2007;Daly, Komaroff, Bloomingdale, Wilson, & Albert, 2001;DeLuca, Johnson, Ellis, & Natelson, 1997) and executive functioning (Claypoole, et al, 2007;Dobbs, Dobbs, & Kiss, 2001), whereas other studies do not (Ross, Fantie, Straus, & Grafman, 2001;Short, McCabe, & Tooley, 2002). Busichio et al (2004), for example, found that CFS patients showed deficits in attention, speed of information processing and motor speed, but not in memory and executive functioning.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to increased physical symptoms after exercise, cognitive function did not deteriorate over time although many studies have reported impairment in cognitive function at baseline (22)(23)(24) or after exercise (11,12,25) for patients with CFS. The reason for this discrepancy may relate to our use of the continuous performance test in this study although one of our previous studies showed that exercise did not alter cognitive function (26).…”
Section: Discussionmentioning
confidence: 84%
“…As noted previously, cognitive dysfunction has been found in some, but not all, neuropsychological studies in CFS patients. For instance, whereas several investigations have shown evidence of impaired memory, attention, and information-processing speed in patients with CFS (Deluca et al, , 1997Dobbs et al, 2001;Joyce et al, 1996), other reports have failed to show any significant cognitive alterations in these patients (Michiels and Cluydts, 2001). This discrepancy between results may be due to the variability of methods of assessment of cognitive function, but also may be due to the relative presence of mental fatigue or other relevant symptoms in the patient populations examined.…”
Section: Discussionmentioning
confidence: 94%